Mapping The Evolving Landscape Of Sustainable Marketing And Climate-Conscious Consumer Behavior: A Bibliometric Analysis Of Global Trends And Digital Shifts (2010–2023) - Fransiskus Novrianto Pakpahan; Andi Azhar (UNIVED Press, 2025)
The urgency of climate change has reshaped the role of marketing in promoting sustainable behaviors and ecological accountability. This study presents a bibliometric analysis of sustainable marketing and consumer behavior literature published between 2010 and 2023. Drawing from Scopus and Web of Science databases, 1433 articles were analyzed using VOSviewer and Biblioshiny to explore co-authorship, keyword co-occurrence, citation, and co-citation networks. The analysis reveals a thematic evolution from product- and firm-centric approaches to consumer-driven narratives that emphasize emotional trust, digital engagement, and intergenerational ethics. The most active contributors include the United States, the United Kingdom, China, and emerging voices from Southeast Asia. Influential authors such as Kumar, White, and Leonidou shaped the field’s theoretical backbone. Three dominant research clusters were identified: behavioral sustainability, digital sustainability communication, and strategic green branding. Methodological advancements include the growing use of data analytics, machine learning, and structural modeling. This study not only maps the intellectual structure of the field but also highlights research gaps in equity, cultural diversity, and AI-based marketing ethics. The findings offer actionable insights for scholars and practitioners seeking to align marketing strategies with global sustainability agendas.